2018
DOI: 10.3390/f9050256
|View full text |Cite
|
Sign up to set email alerts
|

Spruce Budworm (Choristoneura fumiferana Clem.) Defoliation Promotes Vertical Fuel Continuity in Ontario’s Boreal Mixedwood Forest

Abstract: Spruce budworm, Choristoneura fumiferana (Clem.), defoliation has been shown to affect the occurrence of crown fire in Ontario, highlighting the need to better understand the driving factors of this effect on forest structure, including changes in fuel loading, type and position. Here, we investigate five boreal mixedwood sites within four zones that experienced different durations of continuous defoliation by spruce budworm in northeastern Ontario. Duration of defoliation had significant effects on vertical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…The spruce budworm Choristoneura fumiferana , being one of the most dangerous pests of conifers in North America [ 165 ], was selected as a target for screening of anti-insectan metabolites produced by endophytic fungi isolated from needles of some spruce species ( Picea mariana , P. rubens , P. glauca , etc. ), balsam fir ( Abies balsamea ) and American larch ( Larix laricina ).…”
Section: Low-molecular-weight Non-volatile Compoundsmentioning
confidence: 99%
“…The spruce budworm Choristoneura fumiferana , being one of the most dangerous pests of conifers in North America [ 165 ], was selected as a target for screening of anti-insectan metabolites produced by endophytic fungi isolated from needles of some spruce species ( Picea mariana , P. rubens , P. glauca , etc. ), balsam fir ( Abies balsamea ) and American larch ( Larix laricina ).…”
Section: Low-molecular-weight Non-volatile Compoundsmentioning
confidence: 99%
“…Еловая листовёртка-почкоед Choristoneura fumiferana -один из наиболее опасных вредителей хвойных в Северной Америке, который приводит не только к дефолиации деревьев, но и к повышению пожароопасности в лесах (Watt et al, 2018). Этот вид был выбран в качестве мишени для скрининга продуцентов инсектицидных веществ среди эндофитов хвойных.…”
Section: эндофитыunclassified
“…For example, thorough studies of the white spruce (Picea glauca (Moench) Voss) conifer endophyte Phialocephala scopiformis Kowalski DAOMC 229536 have revealed that it produces rugulosin in vitro and in planta, which demonstrates potent insecticidal toxicity to the spruce budworm pest (Miller et al 2008;Sumarah et al 2008;McMullin et al 2018) scopiformis inoculum have been effective in reducing the incidence of spruce budworm, with the endophyte persisting in needles for more than a decade following nursery inoculation (Miller et al 2008;Quiring et al 2020). Spruce budworm outbreaks have devastating defoliation and economic losses across Canada, and therefore the significance of establishing a non-labour intensive, widespread technique that persists for over a decade demonstrates the true potential of conifer endophytes and how their secondary metabolites can be utilized in effective, low-cost pest management strategies (Watt et al 2018). In comparison to traditional mitigation techniques (e.g., aerial application of insecticides) endophytes are more ecologically friendly as they will only impact insects grazing the host.…”
Section: Conifer Endophytes and Their Secondary Metabolitesmentioning
confidence: 99%